Icariin self-crosslinked network functionalized strontium-doped bioceramic scaffolds synergistically enhanced the healing of osteoporotic bone defects. (15th April 2022) - Song, Tao; Yang, Jirong; Liu, Puxin; Liu, Minjun; Li, Dongxiao; Xiao, Yumei; Wang, Yan; Zhang, Xingdong
Abstract: The regeneration of osteoporotic defects remains a great challenge in clinic, due to the capacity of bone regeneration is seriously impaired and bone resorption is overactivated. Although extensive scaffolds are developed to regenerate and remodel osteoporotic bone defects, satisfactory repairing effect has not been achieved yet. Developing a multi-functional scaffold with clinical application prospects is extremely urgent. Herein, an icariin self-crosslinked network functionalized Sr-doped biphasic calcium phosphate bioceramic (IC/Sr-BCP) was developed in an easy and convenient way. The in vitro results showed that both icariin and Sr 2+ could sustained-release from the IC/Sr-BCP scaffold and create an instructive microenvironment for synergistically promoting osteogenesis through activating Wnt/β-catenin and BMP-2/Smad pathways. In addition, osteoclastogenesis was significantly suppressed by icariin and Sr 2+ resulting from the inhibition of nuclear factor-κB (NF-κB) and p38 mitogen-activated protein kinase (p38-MAPK) pathways. The in vivo results suggested that the IC/Sr-BCP scaffold exhibited dual regulation of bone formation and resorption, achieving the synergistic enhancement on bone regeneration than which with only one agent (Sr-BCP or IC/BCP). Moreover, the results also elaborated the underlying mechanisms of these beneficial effects. We believe that it provides a promising strategy for clinical treatment by means of designing multi-functional scaffolds (IC/Sr-BCP) to repair osteoporotic defects. Graphical abstract: Image 1